A case study of the impact of a teacher education course on two Iranian EFL teachers’ beliefs and practices about grammar teaching - Mostafa Nazari; Azadeh Boustani; Mohammad Sheikhi (Asian-Pacific Journal of Second and Foreign Language Education, 2022)
Abstract Despite the substantial growth of research on teachers’ beliefs and practices in the past decades, little research has examined the impact of teacher education on in-service teachers’ grammar beliefs and practices. The present study aimed to fill part of this gap in relation to two Iranian novice EFL teachers. Data were collected before and after a grammar-oriented teacher education course from semi-structured interviews and classroom observations. The findings showed that the course influenced the teachers’ beliefs to move from a more teacher-fronted approach toward an approach that marked attention to the importance of learners’ socioemotional states. Moreover, the teachers’ practices after the course featured more attention to the collaborative and pragmatic aspects of grammar instruction. Based on the findings, we provide several implications for teacher education, which highlight the role of sociocultural and personal dimensions in programs that are structured around grammar instruction.